Subventricular Zone Cell Migration: Lessons from Quantitative Two-Photon Microscopy - James, Rachel; Kim, Yongsoo; Hockberger, Philip; Szele, Francis G. (Frontiers in Neuroscience, 2011)
Neuroblasts born in the adult subventricular zone (SVZ) migrate long distances in the rostral migratory stream (RMS) to the olfactory bulbs where they integrate into circuitry as functional interneurons. As very little was known about the dynamic parameters of SVZ neuroblast migration, we used two-photon time-lapse microscopy to analyze migration in acute slices. This involved analyzing 3-dimensional stacks of images over time and uncovered several novel aspects of SVZ migration: chains remain stable, cells can be immotile for extensive periods, morphology does not necessarily correlate with motility, neuroblasts exhibit local exploratory motility, dorsoventral migration occurs throughout the striatal SVZ and neuroblasts turn at distinctive angles. We investigated these novel findings in the SVZ and RMS from the population to the single cell level. In this review we also discuss some technical considerations when setting up a two-photon microscopic imaging system. Throughout the review we identify several unsolved questions about SVZ neuroblast migration that might be addressed with current or emerging techniques.